A knock study of hydrogen-fueled Wankel rotary engine. (1st August 2022) - Meng, Hao; Ji, Changwei; Yang, Jinxin; Chang, Ke; Xin, Gu; Wang, Shuofeng
Highlights: Knock of hydrogen-fueled Wankel rotary engine is investigated in this work. Effect of ignition timing, spark plug location and number, λ and speed are studied. Knock intensity with distribution, knock duration and cyclic variation are analyzed. All of aspects studied in this work have significant effects on the knock. Abstract: Hydrogen-fueled Wankel rotary engine (HWER) is an excellent power device with superior power and emission performances. Besides, unlike hydrogen-fueled reciprocating piston engines, HWRE is less prone to backfire due to its structural advantages. However, limited by its long combustion chamber, knock, one of abnormal combustion in engines, still hinders the development of HWER. Hence, based on this consideration, the goal of this work is to investigate the knock of HWRE from different aspects, including ignition timing, spark plug number, spark plug location, excess air ratio and engine speed, to provide relevant information for the design of hydrogen-specific WRE. The results show that the knock intensity gradually increases as the ignition timing is advanced, the excess air ratio is decreased and the engine speed is increased, but the knock duration shows different variations. Adopting dual spark plugs tends to lead to stronger knock caused by unstable combustion of hydrogen, while only adopting leading spark plug tends to lead to the knock caused by auto-ignition. When dual spark plugs are used, the leading spark plug is more responsible for the knock caused by unstable combustion and the trailing spark plug is more responsible for the knock caused by auto-ignition.